Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
[tex]4(3q-2)=16q\\\\12q-8=16q\ \ \ \ \ \ |add\ 8\ to\ both\ sides\\\\12q=16q+8\ \ \ \ \ \ |subtract\ 16q\ from\ both\ sides\\\\-4q=8\ \ \ \ \ \ \ |divide\ both\ sides\ by\ (-4)\\\\\boxed{q=-2}[/tex]
[tex] 4\cdot (3q - 2) =16q[/tex]
We first multiply the expression in parentheses by 4:
[tex] 4\cdot 3q - 4\cdot 2 = 16q [/tex]
[tex] 12 q - 8 = 16 q [/tex]
Then, we move expression with q to the left hand side and constant to the right hand side:
[tex] 12q - 16q = 8 [/tex]
[tex] -4q = 8 [/tex]
We divide both sides by (-2):
[tex] q = -2 [/tex]
We first multiply the expression in parentheses by 4:
[tex] 4\cdot 3q - 4\cdot 2 = 16q [/tex]
[tex] 12 q - 8 = 16 q [/tex]
Then, we move expression with q to the left hand side and constant to the right hand side:
[tex] 12q - 16q = 8 [/tex]
[tex] -4q = 8 [/tex]
We divide both sides by (-2):
[tex] q = -2 [/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.